Carcinogenic Methyl Orange Dye Sequestration Using Boron Carbide-Filled-Polypyrrole Composites from Wastewater - Sen, Elif; Mus, Zeynep; Ugraskan, Volkan; Isik, Birol (KOREAN FIBER SOC, 2023)
In this paper, polypyrrole (PPy) composites (PPy-BC) filled with boron carbide (BC) at different ratios were synthesized for the sorption of carcinogenic methyl orange (MO) dye from aqueous media. In sorption experiments, first, optimum process parameters including operating time (0-210 min), adsorbent mass (0.01-0.30 g/50 mL), concentration (10-50 mg/L), and pH (2-12) were determined. The raw data obtained from the sorption tests were applied to the various isotherms and the Langmuir model showed the best results. From Langmuir isotherm model, the maximum sorption capacities for pristine BC, pristine PPy, and PPy-BC-10 composite were calculated as 208.3, 285.7, and 222.2 mg/g at 25 & DEG;C, pH 7, and 10-50 mg/L, respectively. It was determined that the sorption process followed the pseudo-second-order kinetic and the chemisorption process occurred. From the enthalpy values, it was determined that the process was endothermic for pristine BC (+ 40.82 kJ/mol) and pristine PPy (+ 27.33 kJ/mol), and exothermic for PPy-BC-10 (- 7.48 kJ/mol). It can be said that the sorption process of MO dye on composites can be realized by electrostatic interactions, & pi;-& pi; interactions, H-bonding, and pore diffusion. All results showed that the prepared composites could be used as an efficient and potential adsorbent in the sorption of anionic pollutants from an aqueous environment.
Keywords: Sorption; Methyl orange; Polypyrrole; Boron carbide; Composite; POLYAMINE RESIN SYNTHESIS; ANIONIC DYES; ADSORPTIVE REMOVAL; AQUEOUS-SOLUTIONS; ADSORBENT; KINETICS; ISOTHERM; BLUE; THERMODYNAMICS; POLYANILINE; Materials Science; Polymer Science